2016
DOI: 10.3892/ol.2016.5300
|View full text |Cite
|
Sign up to set email alerts
|

FRAT1 expression regulates proliferation in colon cancer cells

Abstract: Abstract. Colorectal cancer is one of the most common gastric malignancies worldwide. However, the underlying mechanism of colon cancer development and valuable indicators of the disease remain unclear. In this study, the expression of frequently rearranged in advanced T-cell lymphomas 1 (FRAT1) in colon cancer was investigated and the association between FRAT1 expression and biological properties of tumors was analyzed. A total of 147 colon cancer tissue samples and adjacent normal tissues were collected betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The primers were as follows: ARHGAP24, 5′-AACTCCTGTCGCTCTTCTACC-3′ and 5′-GCTGTTGCCCACAAATGTCTC-3′; p53, 5′-CCACCATCCACTACAACTAC-3′ and 5′-AAACACGCACCTCAAAGC −3′; GAPDH, 5′-CACCCACTCCTCCACCTTTG-3′ and 5′-CCACCACCCTGTTGCTGTAG-3′. The RT-qPCR was conducted as the following procedure: cycle 1, 95°C for 10 min; cycle 2 with 40 repeated cycles of 95°C for 15 sec, 60°C for 45 sec, and then 95°C for 15 sec, 60°C for 1 min for one cycle; 95°C for 15 sec, 60°C for 15 sec for one cycle ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primers were as follows: ARHGAP24, 5′-AACTCCTGTCGCTCTTCTACC-3′ and 5′-GCTGTTGCCCACAAATGTCTC-3′; p53, 5′-CCACCATCCACTACAACTAC-3′ and 5′-AAACACGCACCTCAAAGC −3′; GAPDH, 5′-CACCCACTCCTCCACCTTTG-3′ and 5′-CCACCACCCTGTTGCTGTAG-3′. The RT-qPCR was conducted as the following procedure: cycle 1, 95°C for 10 min; cycle 2 with 40 repeated cycles of 95°C for 15 sec, 60°C for 45 sec, and then 95°C for 15 sec, 60°C for 1 min for one cycle; 95°C for 15 sec, 60°C for 15 sec for one cycle ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The gene is involved in the process of carcinogenesis in CRC by the Wnt/β-catenin pathway. According to Zhu et al, FRAT1 regulates the proliferation in colon cancer cells and constitutes a potential target for the treatment of CRC (Zhu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of novel biomarkers and an ------------------------------------------------------------------------------------------------------------------------------- The Wnt/β-catenin signaling pathway is highly conserved in metazoan organisms and serves a critical role in embryonic development and carcinogenesis (36,37). as a positive regulator of Wnt/β-catenin signaling, FraT1 is highly upregulated in various human cancers, such as non-small cell lung cancer (nSclc) (17,38), chondrosarcoma (39), ovarian cancer (18), colon cancer (19), gastric cancer (12) and esophageal cancer (20). This upregulation commonly leads to high malignant potential, growth to the point of lethality, and subsequently, poor patient prognosis in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…FraT1 positively regulates the Wnt/β-catenin signaling pathway by inhibiting the activity of GSK-3β toward β-catenin (14)(15)(16). aberrant activation of FraT1 promotes Wnt/β-catenin signaling pathway dysregulation and FraT1 is highly upregulated in a variety of human cancers (12,(17)(18)(19)(20). our previous study demonstrated that FraT1 is an important factor for the development of gliomas, as well as for predicting patient prognosis.…”
Section: Introductionmentioning
confidence: 98%